2013
DOI: 10.1128/aem.00986-13
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lysine Content Is the Main Characteristic of the Soluble Form of the Polyamide Cyanophycin Synthesized by Recombinant Escherichia coli

Abstract: bCyanophycin, a polyamide of cyanobacterial or noncyanobacterial origin consisting of aspartate, arginine, and lysine, was synthesized in different recombinant strains of Escherichia coli expressing cphA from Synechocystis sp. strain PCC 6308 or PCC 6803, Anabaena sp. strain PCC 7120, or Acinetobacter calcoaceticus ADP1. The molar aspartate/arginine/lysine ratio of the water-soluble form isolated from a recombinant strain expressing CphA 6308 was 1:0.5:0.5, with a lysine content higher than any ever described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 31 publications
(57 reference statements)
3
38
0
Order By: Relevance
“…Several theories, including differences in the structure of the polymer; variations in the cell milieu influencing the specificity of the cyanophycin synthetase; or the incorporation of alternative constituents, like Lys, citrulline, and ornithine, have been discussed (6,8). We are now confident that we have identified one of the factors leading to the formation of soluble CGP in E. coli.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Several theories, including differences in the structure of the polymer; variations in the cell milieu influencing the specificity of the cyanophycin synthetase; or the incorporation of alternative constituents, like Lys, citrulline, and ornithine, have been discussed (6,8). We are now confident that we have identified one of the factors leading to the formation of soluble CGP in E. coli.…”
Section: Discussionmentioning
confidence: 82%
“…Pseudomonas putida, for example, synthesized soluble CGP only when cultivated at an elevated temperature of 37°C, while insoluble CGP was formed only at the usual growth temperature of 30°C (8). Several studies on Escherichia coli showed that synthesis of soluble CGP occurred only at a temperature of 30°C or less, while cells of the same strain grown at 37°C contained much less or no soluble CGP (6,14). Another theory suggested that the increased amounts of alternative constituents influenced the solubility or the structure of CGP, or both (6).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These ratios suggest that this is a typical cyanophycin polymer with an aspartate backbone and arginine and lysine side chains, since aspartate accounts for 50% of the residues and the other two amino acids account for the remaining 50%. The solubility of cyanophycin is affected by the lysine content (28), and recombinant cphA genes from other bacteria expressed in E. coli produce soluble cyanophycin with increased lysine content (55). This makes it difficult to predict if cyanophycin exists in a soluble or insoluble form in C. perfringens.…”
Section: Discussionmentioning
confidence: 99%